Productivity and nutritive value of Brachiaria mulato and Centrosema pascuorum mixtures at various ratios in Bauchi State, Nigeria - Sani, Ibrahim; Bello, Khadijat Musa; Abubakar, Mohammed; Nuhu, Sani Hussain (Journal of Pure and Applied Agriculture, 2024)
This study was carried out in 2023 at the Pasture plot of the Department of Animal Production Teaching and Research Farm, Abubakar Tafawa Balewa University, Gubi Campus, Bauchi State. Grass-legume mix ratios of Brachiaria mulato (BM) and Centrosema pascuorum (CP) at different mix rates (B. mulato only, 3 part B.M: 1 part C.P, 1 part B.M: 1 part C.P, 1 part B.M: 3 parts C.P and C. pascuorum only) were studied to determine their growth rate, yield and quality of the forages. Forages across treatments were fertilized at 150 kg/ha of Single Super Phosphate (SSP) in full application at 2 and 5 weeks of age. Plant mix ratios constituted the main plots and stage of harvest (4, 6, 8, 10 & 12 weeks) were the sub factor in a Completely Randomized Block Design layout. The highest (P<0.05) plant height was obtained at 1B.M: 3C.P plant mix ratio for both B. mulato (57 cm) and C. pascuorum (67.67 cm) plants separately. Plant height and tiller number were observed to have increased (P<0.05) as pasture weeks increased from week 4 to 6. Soil cover percentage was significant (P<0.05) and was highest (80.30%) in sole C. pascuorum followed by 53.33% in sole B. mulato and 1B.R: 1C.P mixtures. Plant mix rates significantly (P<0.05) increased leaf area index (LAI) and dry matter yield of B. mulato & C. pascuorum mixtures. The highest (P<0.05) total fresh (32.90 t/ha) and dry matter yield (10.31 t/ha) were in 1BM: 3C.P mix ratio at week 12 (31.55 & 9.35 t/ha, respectively). Similarly, the chemical composition showed 1BM:3C.P had the best (P<0.05) Crude protein (16.02%), NDF (51.94%) and ADF (40.98%) values compared to other treatments except sole C. pascuorum while week 10 had the best CP (17.28%), NDF (49.01%) and ADF (44.53%). Hence, B. mulato and C. pascuorum are recommended for planting at a mixed rate of 1B.M: 3C.P (1: 3) and harvested at 10 weeks old for best productivity for improved animal production.